The Role of Leadership in the effectiveness of archives management in Gowa Regency South Sulawesi Indonesia - Henni Zainal; Aslinda Aslinda; Muhammad Luthfi Siraj (Jurnal Ad'ministrare, 2023)
Leadership is a factor that determines the success or action of an organization, both government and private. The arrangement of archives carried out in an agency is very influential on the smooth running of the leadership's duties. The need to increase awareness of the importance of the role of information for leaders in solving problems today is lacking or even inadequate, this greatly influences the decisions to be taken by organizational leaders. This statement clearly illustrates the importance of information such as archives in every decision-making by leaders. The purpose of this study was to determine the influence of leadership on the effectiveness of filing management at the Pattallasang District Office, Gowa Regency. The type of research in this research is quantitative. Research on the Effectiveness of Archives Management at the Pattallassang District Office, Gowa Regency uses a descriptive approach because this research wants to describe the factors that influence the effectiveness of archives management by comparing several factors that influence the effectiveness of archives management. The sample in this study were all employees, part-time employees and heads of the Pattallassang sub-district office, Gowa Regency, with a total of 33 employees. The conclusion in this study is that the leadership factor influences the effectiveness of archives management with a very good effectiveness. Judging from the leadership factor, because this factor is in a very good qualification, it needs to be maintained or improved so that it becomes even better.